SCAFFOLDING FROVIDED BY A TEACHER IN TEACHING WRITING NEWS ITEM TEXT - DEWI, Mayang Sari Nirmala (2012)
The research centers around the issue about the implementation of scaffolding in teaching writing in an EFL context. The research particularly aims at investigating types of scaffolding, the ways a teacher provides scaffolding, and benefits and challenges of scaffolding in teaching writing News Item text in tenth graders in a senior high school in Bandung, West Java.This research employed a qualitative research design, embracing characteristic of a case study. The data were obtained from non-participant classroom observation for six meetings, and one interview. The data collected from classroom observation and interview were transcribed and then analyzed by using framework of types of scaffolding (e.gRoehler and Cantlon (1997), Hammond (2001), Gibbons, (2002), and Walqui (2006)). In addition, the data also were analyzed using the framework of curriculum-cycle (Derewianka, 1990; Hammond, 2001; Gibbons, 2002, and Emilia, 2010).The findings revealed that seven types of scaffolding were provided by the teacher during teaching writing News Item text. The most intensive scaffolding was given in the Modeling stage, while scaffolding was removed in the Independent Writing stage. Regarding the benefits and challenges of providing scaffolding, this research found out the benefits of scaffolding such as to connect students' prior knowledge with a new concept, to engage students, to minimize the level confusion of students, and to build students' self-confidence. Meanwhile, the challenges of providing scaffolding are the number of students in the classroom, time constraints, and demands on teacher.It is recommended that further research uses a bigger number of subjects in different context to get richer and more reliable data or further research should be also directed toward discovering student's interaction to find out another dimension in scaffolding.Keywords: Scaffolding, Teaching Writing, News Item text, Senior High School